Welfare gains and losses under the Malaysian rice pricing policy and their relationships to the self-sufficiency level - Nik Hasim Mustapha (Penerbit Universiti Kebangsaan Malaysia, 1998)
An applied welfare economics approach was utilised to analyse the impact of public policy on the rice industry arising from the adoption of a price control programme. Taking market clearing equilibrium price under the assumption of a closed economy, the imposition of price control was found to favour consumers at the expense of producers. Based on the 1992 equilibrium price level, welfare gain accrued to the consumers as represented by the consumeris surplus, was estimated at consumers as represented by the consumeris surplus, was estimated at RM205 thousand per year, while a reduction in the producer's surplus, constituting a welfare loss, was estimated at RM188 thousand. Excess demand resulting from the existing pricing policy was supplemented by rice imports, amounting to 2,535 metric tons during the year. The amount of government spending on rice import was RM248 thousand for the year. In total, there was a negative net welfare effect of RM232 thousand for the year analysed. The paper also discussed the interrelationship between pricing policy and the level of self-sufficiency, since for every level of controlled prices, corresponding quantities of rice supplied and demanded can be obtained. Hence, an appropriate pricing policy may be chosen to acquired level of rice self-sufficiency in the industry